Effect of Estrogen on Bronchiolar Smooth Muscle and Peri-Bronchial Lymphocytic Infiltration in Adult Male Mice - Mamoona Shafiq, Amna Faruqi, Quratulain Zia, Erum Afaq, Sadia Mubarak, Tooba Zafar (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To study the effect of estrogen on lungs of adult male mice by assessing and comparing the following histological parameters including bronchiolar smooth muscle size and peri-bronchial lymphocytic Infiltration. Study Design: Randomized control trial Place and Duration of Study: National institute of Health sciences, Islamabad from 1st October 2018 to 31st July 2019. Methodology: Ninety BALB/c mice divided into 2 groups (n=30 per group) were enrolled. The control (male) group received only distilled water, while the interventional groups received pills (estradiol valerate) mixed in distal water according to body weight of the mice for (60) day. Results: 10% of the total mice had nil, 60% had mild, 30% of the total showed moderate while no severe peri-bronchiolar lymphocytic infiltration in response to estrogen. The results also showed that estrogen produced marked hyperplasia of bronchial smooth muscle cells. Conclusion: Estrogen is the sexual hormones which modulate inflammatory processes in the lungs producing pulmonary inflammatory responses leading to asthma and causes hyperplasia of the bronchiolar smooth muscles. Keywords: Estrogen, Asthma, Bronchiolar smooth muscle, Peri-bronchial lymphocytic infiltration, BALB/c mice